The Influence Of Work-Family Conflict And Work Exhaustion On Turnover Intention: The Mediating Role Of Work Stress - Survival; Alfiana; Nur Hasanah, Afifah (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2024)
The aim of this research is to determine the effect of work-family conflict and work exhaustion on turnover intention mediated by work stress in employees of PT Firad Mandiri in Sorowako, East Luwu Regency, South Sulawesi Province. This research approach uses quantitative-explanatory. Data collection methods are in the form of questionnaires, interviews and documentation, with the types of data namely primary data from the results of filling out questionnaires distributed to all data providers from respondents and secondary data obtained from the Human Resources Development section of PT Firad Mandiri with predetermined criteria. The results of the study show that work-family conflict and work exhaustion have a significant effect on turnover intention, work-family conflict and work exhaustion have a significant effect on work stress, work stress has no significant effect on turnover intention, work stress has no effect in mediating the relationship between work-family conflict on turnover intention, and work stress have no effect in mediating the relationship between work exhaustion and turnover intention.